Let off the leash: kala-azar following the use of tumour necrosis factor antibodies. (13th October 2010) - Khan, Anjum; Coakley, Gerald; Cosgrove, Catherine; Lockwood, Diana
Abstract : A 74-year-old woman with a history of psoriatic arthritis was referred to the Hospital for Tropical Diseases following investigation of a skin lesion that had failed to heal after a visit to Malta 2 years previously. Skin biopsy had revealed invasion of Leishmania amastigotes. She reported a recent history of weight loss, dry cough and dyspnoea, and was investigated for pancytopenia and hepatosplenomegaly. Bone marrow biopsy confirmed the diagnosis of visceral leishmaniasis and she responded well to treatment with intravenous liposomal amphotericin B. Recent rheumatological treatment with adalimumab, a monoclonal antibody to tumour necrosis factor α, was thought to be the factor responsible for causing the cutaneous lesion to become disseminated. This case highlights an unexpected adverse effect of novel immunosuppressants. As the use of biologics becomes widespread, there is an increasing need for clinical surveillance.